Effect of precipitates on the austenite grain growth of titanium microalloyed high performance steel - LUO Xu; YANG Cai-shui; KANG Yong-lin; LI Jun-hong (工程科学学报)
An austenite grain growth model was established by analyzing the quantificational relationship between precipitates and austenite grain size. The austenite grain size of Ti microalloyed steel with the interaction of TiN and TiC panicles was calculated by using the austenite grain growth model. The calculated resuhs of the precipitation particle theory indicate that the volume fraction of precipitates gradually decreases and the panicle radius increases with increasing temperature. The austenite grain growth is strongly impeded by TiC panicles, while the pinning force of TiN on austenite grains is weak. The austenite grain size of the tested steels was measured by a test method at different heating temperatures within 30 min. The results are in good agreement with theoretical calculations.